Enhancing in-house plasmid dna extraction using customized glass fiber membrane - Jamel, Jazmi Aiman (Universiti Sains Malaysia, 2025)
Plasmid DNA extraction and purification from bacterial cells are the foundations of many biotechnological processes. The extracted plasmid can be used for a variety of purposes, including genetic research, forensic analysis, and medical diagnosis. In-house extraction kits that are more cost effective and can produce comparable results to the commercial ones are still being pursue by many researchers. In this study we aimed to develop an in-house glass fiber membrane based plasmid extraction kit and compare its yield and purity with commercial kit. The commercial reference kits used in this study will be the Qiagen plasmid extraction kit. The in-house columns with different pore sizes (0.22 μm, 0.45 μm, and 0.80 μm) and number of membrane layers (1, 2 and 6 layers) were self-assembled. The membrane pore size of 0.80 μm yield the highest DNA concentration. the column assembled with 2 layers of GF-0.80 membrane produced highest DNA yield during DNA extraction. The final optimized in-house glass fiber membrane method showed comparable yield and purity (P>0.05) results to the commercial Qiagen plamid DNA extraction kits